2024
DOI: 10.1002/rmv.2509
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and outcomes of upper gastrointestinal bleeding in COVID‐19: A systematic review and meta‐analysis

Sawai Singh Rathore,
Zario Shai Wint,
Aman Goyal
et al.

Abstract: Upper gastrointestinal bleeding (UGIB) in COVID‐19 presents challenges in patient management. Existing studies lack comprehensive review due to varied designs, samples, and demographics. A meta‐analysis can provide valuable insights into the incidence, features, and outcomes of UGIB in COVID‐19. A comprehensive literature search was carried out using several databases. We considered all appropriate observational studies from all over the world. Mantel‐Haenszel odds ratios and associated 95% confidence interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Although saffron shows promise as a preventive and adjunct treatment for COVID-19, further research, particularly through randomized clinical trials using inflammatory biomarkers, is needed to establish its clinical efficacy, especially in resource-poor settings where access to pharmaceutical drugs is limited 56 . Furthermore, Rathore et al 57 have found that whether saffron can act as an adjunct treatment along with standard of care management for frequently encountered complications with high risk of morbidity and mortality in patients with COVID-19, such as upper gastrointestinal bleeding, heart failure, and respiratory failure is unclear.…”
Section: The Role Of Saffron In Male Reproductive Healthmentioning
confidence: 99%
“…Although saffron shows promise as a preventive and adjunct treatment for COVID-19, further research, particularly through randomized clinical trials using inflammatory biomarkers, is needed to establish its clinical efficacy, especially in resource-poor settings where access to pharmaceutical drugs is limited 56 . Furthermore, Rathore et al 57 have found that whether saffron can act as an adjunct treatment along with standard of care management for frequently encountered complications with high risk of morbidity and mortality in patients with COVID-19, such as upper gastrointestinal bleeding, heart failure, and respiratory failure is unclear.…”
Section: The Role Of Saffron In Male Reproductive Healthmentioning
confidence: 99%